2009
DOI: 10.1603/022.038.0218
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cover Crop and Intercrop Systems onBemisia argentifolli(Hemiptera: Aleyrodidae) Infestation and Associated Squash Silverleaf Disorder in Zucchini

Abstract: Field experiments were conducted to evaluate the effects of cover cropping and intercropping on population densities of silverleaf whitefly, Bemisia argentifolli Bellow and Perring, and the incidence of squash silverleaf disorder (SSL) in zucchini, Cucurbita pepo L., in Oahu, HI. Two cover crops, buckwheat (BW), Fagopyrum esculentum Moench, and white clover (WC), Trifolium repens L., or sunn hemp (SH), Crotolaria juncea L., and an intercropped vegetable, okra, Abelmonchus esculentus L., were evaluated during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…This was shown in a similar study where yields of zucchini plants inter-planted into a buckwheat (Fagopyrum esculentum Moench) and white clover (Trifolium repens L.) living mulch were significantly higher than in monoculture plots (Manandhar et al 2009;. …”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…This was shown in a similar study where yields of zucchini plants inter-planted into a buckwheat (Fagopyrum esculentum Moench) and white clover (Trifolium repens L.) living mulch were significantly higher than in monoculture plots (Manandhar et al 2009;. …”
Section: Discussionsupporting
confidence: 59%
“…Companion plants have been shown to reduce pest populations and damage by functioning as physical barriers, camouflaging host plants and deterring pest colonization (Hooks et al 1998;Boucher & Durgy 2004;Frank & Liburd 2005;Cavanagh et al 2009;Manandhar et al 2009). Additionally, several studies have shown that the companion planting tactic can be effectively used to delay the onset of insect caused plant diseases and phytotoxemias in cucurbit crops (Frank & Liburd 2005;Nyoike et al 2008;Manandhar & Hooks 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), lady beetles, lacewings, spiders, assassin bugs, minute pirate bugs, and ground beetles. Careful timing of the planting of insectary plants can help enhance population densities of predatory insects or insect parasitoids that could result in a reduction of insect transmitted viral diseases (Mandanhar et al 2009). …”
Section: Enhancing High Biological Diversity and Promoting Natural Enmentioning
confidence: 99%
“…Cover crops are well known and used for their ability to increase soil quality features but their potential use as a tool to help suppress insect pest populations is less recognized. However, cover crops in the form of plant diversification can be used to help mitigate problems associated with insect pests, directly through reduced colonization (Frank and Liburd 2005) and indirectly by decreasing the occurrence of insect caused plant viruses and phytotoxemias (Hooks and Fereres 2006;Manandhar et al 2009). Cruciferous crops are probably the most studied plants with respect to evaluating the impact of plant mixtures on insect population dynamics (Hooks and Johnson 2003).…”
Section: Introductionmentioning
confidence: 99%